Ergonomic lumbar support - Karuppiah, Karmegam; Salit, Mohd Sapuan; Ismail, Mohd Yusof; Ismail, Napsiah; Mani, Kulanthayan K.C.; Md. Ali, Nazrol (2013)
A vehicle includes a seat on which a rider and co-rider sit and at least one backseat for supporting a back of the rider and the co-rider. The backseat being internally provided with an ergonomic lumbar support assembly capable of providing adjustable support to varying postures of the rider and the co-rider includes a pair of base plate members, at least one rod steel member, a first pair of vertical columns and a second pair of vertical columns extending upwards mounted on the pair of base plate members and at least one movable seat frame means operably coupled to the first pair of vertical columns and/or the second pair of vertical columns.